On unitary reconstruction of linear optical networks. (23rd September 2016) - Tillmann, Max; Schmidt, Christian; Walther, Philip
Abstract: Linear optical elements are pivotal instruments in the manipulation of classical and quantum states of light. Recent progress in integrated quantum photonic technology enabled the implementation of large numbers of such elements on chip, in particular passively stable interferometers. However, it is a challenge to characterize the optical transformation of such a device as the individual optical elements are not directly accessible. Thus only an effective overall transformation can be recovered. Here we present a reconstruction approach based on a global optimization of element parameters and compare it to two prominently used approaches. We numerically evaluate their performance for networks up to 14 modes and various levels of error on the primary data.